Breeding for Resilience to Water Deficit and Its Predicted Effect on Forage Mass in Tall Fescue - Blair L. Waldron (MDPI AG, 2021)
Resilience is increasingly part of the discussion on climate change, yet there is a lack of breeding for resilience per se. This experiment examined the genetic parameters of a novel, direct measure of resilience to water deficit in tall fescue (Lolium arundinaceum (Schreb.) Darbysh.). Heritability, genetic correlations, and predicted gain from selection were estimated for average productivity, resilience, and stability based on forage mass of a tall fescue half-sib population grown under a line-source irrigation system with five different water levels (WL). Resilience was both measurable and moderately heritable (h2 = 0.43), with gains of 2.7 to 3.1% per cycle of selection predicted. Furthermore, resilience was not correlated with average response over environments and negatively correlated with stability, indicating that it was not a measure of responsiveness to more favorable environments. Genetic correlations among WL ranged from 0.87 to 0.56, however in contrast, resilience was either not or slightly negatively genetically correlated with WL except for moderate correlations with the ‘crisis’ WL. Thus, breeding for improved resilience was predicted to have little effect on forage mass at any given individual water deficit environment. Overall, results indicated that this novel metric could facilitate breeding for improved resilience per se to water deficit environments.